Disruption of Extracellular Matrix and Perineuronal Nets Modulates Extracellular Space Volume and Geometry - Syková, Eva; Voříšek, Ivan; Starčuk, Zenon; Kratochvíla, Jiří; Pavlova, Iveta; Ichikawa, Yuki; Kwok, Jessica C F; Kmoníčková, Eva; Myronchenko, Svitlana; Hromádka, Tomáš; Smolek, Tomáš; Avila, Martin; et al. (The Journal of neuroscience, 2025)
Extracellular matrix (ECM) is a network of macromolecules which has two forms-perineuronal nets (PNNs) and a diffuse ECM (dECM)-both influence brain development, synapse formation, neuroplasticity, CNS injury and progression of neurodegenerative diseases. ECM remodeling can influence extrasynaptic transmission, mediated by diffusion of neuroactive substances in the extracellular space (ECS). In this study we analyzed how disrupted PNNs and dECM influence brain diffusibility. Two months after oral treatment of rats with 4-methylumbelliferone (4-MU), an inhibitor of hyaluronan (HA) synthesis, we found downregulated staining for PNNs, HA, chondroitin sulfate proteoglycans, and glial fibrillary acidic protein. These changes were enhanced after 4 and 6 months and were reversible after a normal diet. Morphometric analysis further indicated atrophy of astrocytes. Using real-time iontophoretic method dysregulation of ECM resulted in increased ECS volume fraction α in the somatosensory cortex by 35%, from α = 0.20 in control rats to α = 0.27 after the 4-MU diet. Diffusion-weighted magnetic resonance imaging revealed a decrease of mean diffusivity and fractional anisotropy (FA) in the cortex, hippocampus, thalamus, pallidum, and spinal cord. This study shows the increase in ECS volume, a loss of FA, and changes in astrocytes due to modulation of PNNs and dECM that could affect extrasynaptic transmission, cell-to-cell communication, and neural plasticity.
Keywords: astrocyty; Hymecromone; extracelulární matrix; extracellular matrix; Nerve Net; Hyaluronic Acid; gliový fibrilární kyselý protein; krysa rodu Rattus; hyaluronan synthase; extracelulární prostor; potkani Sprague-Dawley; extracellular diffusion; hymekromon; extracellular transmission; potkani Wistar; Rats, Wistar; Extracellular Space; Astrocytes; Rats, Sprague-Dawley; mužské pohlaví; nervová síť; zvířata; Glial Fibrillary Acidic Protein; Rats; Animals; Extracellular Matrix; Male; mozek; Brain; plasticity; kyselina hyaluronová; perineuronal nets